O papel do acusado para a efetividade do princípio constitucional da ampla defesa: extensão e limites do direito de defender-se por si próprio - Barroso, Marcelo Lopes (2008)
The Brazilian constitutional system shelters a series of procedural guarantees as a way to point out the position of the individual´s prevalence in view of the state. Besides the explicit guarantees listed/enumerated in the Magna Carta´s text, others arise from principles and treaties in which the Federal Republic of Brazil takes part. In this stage of this study, the self-defense is analyzed as a constitutional guarantee. The penal procedure in the 21th century has to be understood, under a constitutional perspective, as a tool to realize the guaranty principles foreseen in the Magna Carta, among them the selfdefense. The practice of the defensive activity by the accused himself, its characterization, amplitude, repercussion and limits is studied. The right to know the accusation is presupposition for the practice of self-defense. The right to defend yourself by yourself, in its positive aspect, is divided in the right of presence, of hearing, to postulate for the own cause and of the right to retainer a lawyer. In its negative aspect, the self-defense involves the privilege against self-incrimination and the right to remain silent. It is dealt with the interrogation during the penal procedure, once it is in this procedural act that the selfdefense finds its greatest expression. It is done research on the new interrogation by videoconference, its compatibility with the principles of penal procedure.